Technological Resources to Prevent Cyberbullying During Adolescence: The Cyberprogram 2.0 Program and the Cooperative Cybereduca 2.0 Videogame - Garaigordobil, Maite; Martínez-Valderrey, Vanesa (Frontiers in Psychology, 2018)
This article describes an intervention proposal, made up of a program (Cyberprogram 2.0 Garaigordobil & Martínez-Valderrey, 2014) and a videogame (Cooperative Cybereduca 2.0 Garaigordobil & Martínez-Valderrey, 2016) which aims to prevent and reduce cyberbullying during adolescence and which has been validated experimentally. The proposal has four objectives: (1) to identify and conceptualize bullying/cyberbullying, and the three roles involved in this phenomenon; (2) to analyze the consequences of bullying/cyberbullying for victims, aggressors, and observers, promoting critical capacity and the capacity to report these actions when they are discovered; (3) to develop coping strategies to prevent and reduce bullying/cyberbullying behaviors; and (4) other related goals. The activities are carried out in the classroom, and the online video is the last activity, which represents the end of the intervention program. The videogame (www.cybereduca.com) is a trivial pursuit game with questions and answers related to bullying/cyberbullying. This cybernetic trivial pursuit is organized around a fantasy story, a comic that guides the game. The videogame contains 120 questions about 5 topics: cyberphenomena, computer technology and safety, cybersexuality, consequences of bullying/cyberbullying, and coping with bullying/cyberbullying. To evaluate the effectiveness of the intervention, a quasi-experimental design, with repeated pretest-posttest measures and control groups, was used. During the pretest and posttest stages, 8 assessment instruments were administered. The experimental group randomly received the intervention proposal, which consisted of one weekly 1-hour session during the entire school year. The results obtained with the analyses of variance of the data collected before and after the intervention in the experimental and control groups showed that the proposal significantly promoted the following aspects in the experimental group: (1) a decrease in face-to-face bullying and cyberbullying behaviors, in different types of school violence, premeditated and impulsive aggressiveness, and in the use of aggressive conflict-resolution strategies; and (2) an increase of positive social behaviors, self-esteem, cooperative conflict-resolution strategies, and the capacity for empathy. The results provide empirical evidence for the proposal. The importance of implementing programs to prevent bullying in all its forms, from the beginning of schooling and throughout formal education, is discussed.